Pengaruh Experiental Marketing Dan Customer Value Terhadap Customer Loyalty Melalui Customer Satisfaction Sebagai Variabel Intervening Pada Pelanggan Café - Indahsari, Lily Nur; Arif, Muhammad; Harahap, Rahmat Daim (CV. ITTC INDONESIA, 2023)
This study aims to examine the Effect of Experiential Marketing and Customer Value on Customer Loyalty through Cutomer Satisfaction as an Intervening Variable in Free Time Cafe Customers in Air Batu, both partially and simultaneously, and also by path analysis. This study used quantitative methods with data collection using Likert scale method. The subjects used in this study were consumers of Leisure Cafe in Air Batu which amounted to 100 people and were taken using axial sampling. Data analysis techniques through IBM SPSS statistical program 25. The results of this study showed that overall for each partial test stated significant and positive effect between variables. Where from the statistical results states the value of α < 0.05. In the path analysis test also states that there is a direct influence and indirect influence on each variable connected through variable z. And also simultaneously shows that there is an influence of Experiential Marketing and Customer Value together affect Customer Loyalty through the variable Customer Satisfaction, based on the calculated F value of 317,643 with a significant value of 0.000 < 0.05. With an efficiency of determination of 80.2%. So the results of the study, as a whole in partial and simultaneous trials state that it is influential and significant.